Hemispheric symmetry and asymmetry of poleward moving radar auroral forms (PMRAFs) and associated polar cap patches during a geomagnetic storm - Zou, Ying; Chen, Li-Jen; Walsh, Brian M.; Burkholder, Brandon; Ma, Yuzhang; Bristow, William A.; Lyons, Larry R.; Liu, Jiang; Tian, Sheng; Yadav, Sneha; Coster, Antea J.; McWilliams, Kathryn A. (Frontiers in Physics, 2023)
Magnetopause reconnection is known to impact the dayside ionosphere by driving fast ionospheric flows, auroral transients, and high-density plasma structures named polar cap patches. However, most of the observed reconnection impact is limited to one hemisphere, and a question arises as to how symmetric the impact is between hemispheres. We address the question using interhemispheric observations of poleward moving radar auroral forms (PMRAFs), which are a “fossil” signature of magnetopause reconnection, during a geomagnetic storm. We are particularly interested in the temporal repetition and spatial structure of PMRAFs, which are directly affected by the temporal and spatial variation of magnetopause reconnection. PMRAFs are detected and traced using SuperDARN complemented by DMSP, Swarm, and GPS TEC measurements. The results show that PMRAFs occurred repetitively on time scales of about 10 min. They were one-to-one related to pulsed ionospheric flows, and were collocated with polar cap patches embedded in a Tongue of Ionization (TOI). The temporal repetition of PMRAFs exhibited a remarkably high degree of correlation between hemispheres, indicating that PMRAFs were produced at a similar rate, or even in close synchronization, in the two hemispheres. However, the spatial structure exhibited significant hemispherical asymmetry. In the Northern Hemisphere, PMRAFs/patches had a dawn-dusk elongated cigar shape that extended >1000 km, at times reaching >2000 km, whereas in the Southern Hemisphere, PMRAFs/patches were 2-3 times shorter. The interesting symmetry and asymmetry of PMRAFs suggests that both magnetopause reconnection and local ionospheric conditions play important roles in determining the degree of symmetry of PMRAFs/patches.